A simplified analytical method for the pressure of tilt hydrostatic journal bearing. Issue 6 (9th July 2018) - Du, Yikang; Mao, Kuanmin; Liu, Hongqi; Mao, Xiaobo; Li, Zhihang
Abstract : Purpose: This paper aims to present a simplified method to predict the pressure of the recess, no matter whether the tilt center coincides with the geometric center of the hydrostatic journal bearings. Design/methodology/approach: To validate the effectiveness of the presented model, computational fluid dynamics (CFD) method and experimental method are performed in this study. Findings: By comparing the CFD results and the experimental results, the pressure of the recess is related to the tilt direction, the tilt center, the width of the land and the circumferential angle of the land. Originality/value: The mathematic model requires equivalent resistance of land edge – tilt position, tilt direction, tilt angle and the thickness of oil film instead of any digital iteration. Furthermore, a novel experimental apparatus including a circular hydrostatic bearing called ball bearing is designed to study the tilt effect produced by manufacturing error and offset load force on the pressure of the recess.